Single nucleiotide polymorphisms on exon 3 of leptin gene and their association with growth in Padjadjaran sheep - Rahmat, D.; Hilmia, N.; Bandiati, S.K. (Journal of the Indonesian Tropical Animal Agriculture, 2020)
The diversity of leptin genes in cattle has an impact to the physiological function of the leptin hormone as anti-obesity. This study was aimed to determine polymorphisms of the Leptin gene based on Single Nucleotide Polymorphism on exon 3rd and their effect to body weight, of Padjadjaran sheep. DNA samples were obtained from the blood of 26 Padjadjaran rams 1 years. Data of leptin gene diversity were analyzed from the results of PCR product sequencing by Sanger Methode of 696 bp leptin exon 3. Point mutations (SNPs) on nucleotide sequence were analyzed using Bioedit and MEGA 7 Program. Growth parameters which were measured i.e. monthly body weight gain until one year of age. The association of leptin gene polymorphism with body weight was find out by unpaired T test. The results showed there were SNPs in Leptin gene in exon 3 of Padjadjaran sheep, namely g.170 G> A and g. 332.A> G. Both of these mutations are non-synonymous mutations because there were altered amino acids from Arginine to Glutamine. Genotyping was done based on the two mutations above and got two alleles G and A, each of which has an allele frequency of 0.75 and 0.25, with the frequency of each genotype, AG and GG was 0.5. There was not association between SNPs on leptin gene with body weight from birth to 12 months of age.